Enhancing cell-mediated immunity through dendritic cell activation: the role of Tri-GalNAc-modified PLGA-PEG nanoparticles encapsulating SR717 - Gong, Yang; Jia, Hongbin; Dang, Wenrui; Zhou, Ting; He, Pu; Wang, Xiaolei; Zhu, Bingdong (Frontiers in Immunology, 2024)
IntroductionVaccines against intracellular pathogens like Mycobacterium tuberculosis (M. tuberculosis) require the induction of effective cell-mediated immunity. Adjuvants primarily enhance antigen-induced adaptive immunity by promoting the activation of antigen-presenting cells (APCs).This study is to develop an adjuvant targeted to dendritic cells (DCs), one of the main APCs, so as to assist in inducing a long-term cellular immune response to M. tuberculosis protein antigens.MethodsPolylactic-co-glycolic acid-polyethylene glycol (PLGA-PEG) nanoparticles (NPs) modified with Triantennary N-Acetylgalactosamine (Tri-GalNAc) were prepared to target DCs. Additionally, the stimulator of interferon genes (STING) agonist SR717 was encapsulated within PLGA-PEG NPs to activate DCs. Meanwhile, M. tuberculosis fusion protein (TP) was encapsulated in PLGA-PEG NPs to construct vaccine candidates: TP/Tri-GalNAc-PLGA-PEG-SR717 (TP/GPS in short) and TP/ Tri-GalNAc-PLGA-PEG (TP/GP in short). The targeting and activation effects of these NPs were assessed in vitro and in vivo, and their immunogenicity were evaluated in mice.ResultsTri-GalNAc modification significantly enhanced the targeting of NPs to DCs, and encapsulated SR717 effectively promoted the maturation and activation of DCs. TP/GPS elicited a potent antigen-specific T cell immune response and successfully induced long-term immune memory in mice. Moreover, after the mice were infected with H37Ra via nasal instillation, TP/GPS significantly reduced the bacterial load in their lungs.DiscussionTri-GalNAc-modified PLGA-PEG NPs in combination with SR717 targeted and activated DCs, effectively assisting M. tuberculosis antigen in inducing long-term T cell-mediated immunity. This approach offers an innovative and effective adjuvant strategy for the development of subunit vaccine against intracellular pathogen.